2010
DOI: 10.1186/1741-7015-8-58
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of pain intensity and persistence in a prospective Italian cohort of patients with herpes zoster: relevance of smoking, trauma and antiviral therapy

Abstract: BackgroundHerpes zoster (HZ) is a common disease, characterized by rash-associated localized pain. Its main complication, post-herpetic neuralgia (PHN), is difficult to treat and may last for months to years in the wake of rash resolution. Uncertainties remain as to the knowledge of predictors of HZ-related pain, including the role of antiviral therapy in preventing PHN in ordinary clinical practice. This prospective cohort study was aimed at investigating pain intensity at HZ presentation and its correlates, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
101
2
10

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(121 citation statements)
references
References 46 publications
(93 reference statements)
8
101
2
10
Order By: Relevance
“…In the chronic phase, 90 % of PHN patients report having difficulty with their usual daily tasks and sleep disturbances [31,32]. PHN is significantly associated with pain intensity at HZ presentation, age, smoking, symptoms of anxiety and depression, trauma, and missed antiviral prescription [33,34].…”
Section: Clinical Aspects and Epidemiologymentioning
confidence: 99%
“…In the chronic phase, 90 % of PHN patients report having difficulty with their usual daily tasks and sleep disturbances [31,32]. PHN is significantly associated with pain intensity at HZ presentation, age, smoking, symptoms of anxiety and depression, trauma, and missed antiviral prescription [33,34].…”
Section: Clinical Aspects and Epidemiologymentioning
confidence: 99%
“…HZ incidence is known to increase in immunodepression, being more frequent and aggressive in transplant recipients, cancer patients, HIV-infected people, and in patients with autoimmune diseases (rheumatoid arthritis and lupus erythematosus sistemicus among others), diabetes, hypertension, renal failure and chronic obstructive pulmonary disease (Hata et al, 2011;Yi et al, 2010;Yang et al, 2011;Schmader et al, 2008). Notwithstanding this evidence, HZ can be considered a disease involving immunocompetent subjects in the vast majority of cases (Hegalsson et al, 2000;Oxman et al, 2005;Yawn et al, 2007;Parruti et al, 2010;. Contacts with patients with Varicella, more frequent for some professionals as pediatricians and teachers, turned out to be protective , in line with the biological assumption that exposure to VZV may boost and strengthen natural cell-mediated immunity (Vossen et al, 2004).…”
Section: Epidemiologymentioning
confidence: 99%
“…Detailed information about pain, clinical aspects and therapy are not usually present in such databases, even though these studies usually include larger number of patients in comparison with prospective collections. In at least two cases, however, prospective evaluation of the incidence of HZ has been attempted in recent years (Oxman et al, 2005;Parruti et al, 2010). The Shingles Prevention Study (Oxman et al, 2005) was a randomized double-blind placebo-controlled trial set up to demonstrate that vaccination against VZV can decrease the incidence and severity of HZ and post herpetic neuralgia (PHN), its more frequent complication.…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…These agents reduce the duration of viral shedding, hasten rash healing, reduce the severity and duration of acute pain, and reduce the risk of progression to PHN [39]. For example, Dworkin et al [40] and Parruti et al [41] done a cohort study of 419 and 519 Hz patients respectively found that patients receiving antiviral therapy in the acute phase had a significantly lower prevalence of PHN.…”
Section: Prevention Of Phnmentioning
confidence: 99%